Diversity of macromoths (Lepidoptera : Heterocera) in Perlis State Park, Kedawi Region, Malaysia : new distributional record of noctuid - Muhamad Ikhwan Idris,; Inda Mastura Ruslan,; Christharina S. Gintoron,; Raziman Imam Ghazali, (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
This study aimed to determine the macromoths species diversity in Perlis State Park, Kedawi Region, Malaysia. Two sampling series were conducted on 17th - 21st April 2015 and 12th - 16th November 2015. Modified Pennsylvanian light trap with 160 W mercury vapor bulb was used to attract the macromoths in ground (≤ 2m) and lower canopy (≥ 20m) levels. A total of 386 individuals comprising 182 species from 13 families were recorded in 10 nights of sampling. The macromoths diversity was considerably high with Fisher’s alpha diversity index of α= 134.5 and Shannon’s diversity index, H’ = 4.777. Noctuidae was the highest family recorded in terms of species number, while family Arctiidae was the highest for the number of individuals collected.